Neuromodulation effect of laser acupuncture on female stress urinary incontinence: a randomized controlled trial - Abdulaziz, Khadiga S.; Mohamed, Mahmoud Hamada; Ahmed Gad, Doha Ramy; El-Din Mahmoud , Lama Saad; Atiya Elshimy, Emad Eldeen; Osman, Doaa A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Although the impact of electroacupuncture or needle acupuncture on stress urinary incontinence (SUI) was previously investigated, there are no previous studies that have investigated the neuromodulatory impact of laser therapy on neurogenic acupoints in women with SUI. The aim of this study was to determine the neuromodulation mechanism of laser therapy on neurogenic acupoints in women with SUI. A prospective, randomized, controlled trial, pre, and post-experimental study was carried out. Thirty women with SUI were equally assigned into two equal groups (control and study groups). The control group received pelvic floor exercises for 6 weeks (n=15), while the study group received the same pelvic floor exercises for 6 weeks in addition to laser acupuncture on neurogenic acupoints (n=15). Before and after rehabilitation, pelvic floor muscle strength (PFMS) was assessed with the XFT-0010 Pelvic Muscle Trainer device, SUI severity was assessed with the Severity Index (SI) for urinary incontinence, and the impact of SUI on quality of life (QOL) was assessed with the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form (ICIQ-SF). Comparison between the two groups after treatment showed a significant improvement in PFMS and significant reductions in scores of SI for urinary incontinence and ICIQ-SF (p<0.05). The neuromodulatory impact of laser application on neurogenic acupoints significantly increases the strength of pelvic floor muscles and significantly decreases the incontinence level and its impact on QOL in women with SUI.